2005
DOI: 10.1186/1471-5945-5-5
|View full text |Cite
|
Sign up to set email alerts
|

Erythroderma: A clinical study of 97 cases

Abstract: Background: Erythroderma is a rare skin disorder that may be caused by a variety of underlying dermatoses, infections, systemic diseases and drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

27
102
6
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(162 citation statements)
references
References 16 publications
(22 reference statements)
27
102
6
14
Order By: Relevance
“…The male female ratio of 4.2:1 correlated with that found by Botella Estradas et al 7 (4:1). In this study, scaling was found in 100% of the cases, which is similar to the observation made by Chaudhary and Gupte, 4 Bharatia PR and Joshi, 8 Akhyani M et al, 9 and Sudho R et al, 10 in their respective studies. Erythema was found in 100% cases in the present study which is similar to the observation made by Hulmani et al, 11 Jowkar F et al, 12 and Akhyani M et al, 9 in their respective studies.…”
Section: Discussionsupporting
confidence: 79%
“…The male female ratio of 4.2:1 correlated with that found by Botella Estradas et al 7 (4:1). In this study, scaling was found in 100% of the cases, which is similar to the observation made by Chaudhary and Gupte, 4 Bharatia PR and Joshi, 8 Akhyani M et al, 9 and Sudho R et al, 10 in their respective studies. Erythema was found in 100% cases in the present study which is similar to the observation made by Hulmani et al, 11 Jowkar F et al, 12 and Akhyani M et al, 9 in their respective studies.…”
Section: Discussionsupporting
confidence: 79%
“…Pruritus has been reported as a predominant symptom in many of the studies including those by Khaled, Sellami and Fazaa (56%), Jowker, Aslani and Shafiee (64.7%), Akhyani and Ghodsi (97.5%). [6][7][8] Sudden progression within a day was seen in drug induced erythroderma as observed in other studies. In patient with erythroderma secondary to lymphoma, it took more than 1 month for generalised spread of the disease.…”
supporting
confidence: 60%
“…[9][10][11] Sigurdsson and Toonstra found edema in 54% of patients, Khaled, Sellami and Fazaa in 23%, Akhyani and Ghodsi in 14%. 2,6,8 In our study 92% of the patients had edema which is much higher compared to other studies. Malnutrition, which is prevalent in our population, might have contributed to the edema in such large number, since hypoalbuminemia was also seen in 67%.…”
contrasting
confidence: 48%
See 1 more Smart Citation
“…Comparable to previous studies, a preexisting dermatoses was present in 76.5% of the patients [9,10]. Hasan et al reported 32% patients with idiopathic erythroderma [11] while in our study, it was only 2.9%.…”
Section: Discussioncontrasting
confidence: 40%